2020
DOI: 10.3390/ph13110347
|View full text |Cite
|
Sign up to set email alerts
|

Role of Kinins in Hypertension and Heart Failure

Abstract: The kallikrein–kinin system (KKS) is proposed to act as a counter regulatory system against the vasopressor hormonal systems such as the renin-angiotensin system (RAS), aldosterone, and catecholamines. Evidence exists that supports the idea that the KKS is not only critical to blood pressure but may also oppose target organ damage. Kinins are generated from kininogens by tissue and plasma kallikreins. The putative role of kinins in the pathogenesis of hypertension is discussed based on human mutation cases on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 220 publications
0
25
0
1
Order By: Relevance
“…We know far less about human PVAT compared to that in rodent models and there are indications that human PVAT has somewhat distinct features relative to mice. In spite of that, recent studies reported that human tPVAT shows some BAT/beige features (for instance Ucp1 expression; Wei et al, 2015 ; Vargas et al, 2018 ; Hamid et al, 2020 ), whereas aPVAT resembles WAT. The plasticity of human PVAT depots in response to thermogenic stimuli is unknown, but a recent study based on autopsies of Siberian adults indicated that almost one half the individuals assessed exhibited multilocular adipocytes, paucilocular adipocytes, and UCP1 expression in mediastinal peri-aortic PVAT ( Efremova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We know far less about human PVAT compared to that in rodent models and there are indications that human PVAT has somewhat distinct features relative to mice. In spite of that, recent studies reported that human tPVAT shows some BAT/beige features (for instance Ucp1 expression; Wei et al, 2015 ; Vargas et al, 2018 ; Hamid et al, 2020 ), whereas aPVAT resembles WAT. The plasticity of human PVAT depots in response to thermogenic stimuli is unknown, but a recent study based on autopsies of Siberian adults indicated that almost one half the individuals assessed exhibited multilocular adipocytes, paucilocular adipocytes, and UCP1 expression in mediastinal peri-aortic PVAT ( Efremova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…2015; Vargas et al, 2018;Hamid et al, 2020), whereas aPVAT resembles WAT. The plasticity of human PVAT depots in response to thermogenic stimuli is unknown, but a recent study based on autopsies of Siberian adults indicated that almost one half the individuals assessed exhibited multilocular adipocytes, paucilocular adipocytes, and UCP1 expression in mediastinal peri-aortic PVAT (Efremova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same diabetes model, the overexpression of human kallikrein promoted neovascularization, suppressed apoptosis, and upregulated endothelial nitric oxide synthase expression, protecting hindlimb from ischemic damage [ 167 ]. Another mechanism for hypoxia could be the impairment of the vascular vasodilatory response since in endothelial cells BK leads to a potent vasodilation response that can be mediated by nitric oxide (NO) through the activation of endothelial NO synthase (eNOS), prostacyclin (PGI 2 ), and endothelial hyperpolarizing factor (EDHF) [ 168 , 169 ]. Interestingly, in the dog model of DMD, vascular endothelial dysfunction was reduced by bradykinin infusion, restoring the response to acetylcholine in the vascular bed, and effect that was dependent on NO, through the upregulation of eNOS and nNOS.…”
Section: Regulation Of Ccn2/ctgf and Fibrosis In Skeletal Muscle: Role Of Vasoactive Peptidesmentioning
confidence: 99%